OXYGEN-DEPENDENT PHAGOCYTOSIS OF BLOOD MONOCYTES IN CHILDREN WITH HELICOBACTER PYLORI-ASSOCIATED GASTRIC AND DUODENAL EROSIONS AND ULCER - Kolenchukova, O. A.; Gvozdev, I. N.; Gorbachova, N. N.; Litvinova, I. S. (Infekt͡s︡ii͡a︡ i immunitet, 2018)
The aim of the research is to study oxygen-dependent phagocytosis of blood monocytes in children with gastric and duodenal erosions  and ulcers by chemiluminescence analysis. The subjects of the  research were blood monocytes, extracted from blood in 44 children  with gastric and duodenal erosions and ulcers in the ages from 11 to  18 years. Microscopic tests for the bioptats of gastric mucosa of  both standard regions and edges of ulcer defects had resulted in the  determination of 2 groups of the patients with gastric and duodenal  erosions and ulcers. The 1st group was represented by Helicobacter  pylori high dissemination. As for the 2nd group, the patients showed  low bacterization. The tests for luminol-dependent hemiluminescence of blood monocytes in patients with H. pylorihigh  dissemination of gastric and duodenal mucosa demonstrated the  significant increase of the intensity and the growth of areas both  under the curve of spontaneous response and under the curve in the  zimozan-induced process as compared to the monocyte activity  in the group with low dissemination. Following the lucigenin- dependent chemiluminescence reactions in the group with H. pylori  high dissemination we had found significant increase of the time of  approaching the peak in both spontaneous response and zimozan- induced processes while the activation index was higher in  comparison with phagocyte activities of monocytes in the group with  low dissemination. Further stage of the research was to identify CagA-positive strains of H. pylori in the children with gastric and  duodenal erosions and ulcers. Studying chemiluminescence activity  of blood lymphocytes in the patients with anti-CagA antibodies we found the true increase of the time of reaching the peak, the  intensity and the area under the curve in spontaneous process in  luminol-dependent response and the time of reaching intensity peak  and the intensity of spontaneous chemiluminescence reaction,  lucigenin being an activator. So we marked the increase of the  activity of oxygen-dependent phagocytosis of blood monocytes in  children with H. pylori associated with gastric and duodenal erosions  and ulcers related to H. pylori increased bacterization. The growth of  H. pylori dissemination results in the higher stage of stomach  mucosa inflammation. Therefore active phagocytes generate more  intensively the formation of active forms of oxygen, free radicals and the products of peroxide oxidation. CagA-positive strains of H. pylori, as a rule, are associated with the higher level of inflammatory  activity than  CagA-negative ones. As a result of such influence the  functional activity of monocytes increases, because they are  «professional » phagocytes. The ability to perform phagocytosis is better expressed in them as compared to other leukocytes.